2005
DOI: 10.1161/01.hyp.0000156538.59873.86
|View full text |Cite
|
Sign up to set email alerts
|

High Heritability of Ambulatory Blood Pressure in Families of East African Descent

Abstract: Abstract-We estimated the heritability of ambulatory systolic blood pressure (SBP), diastolic blood pressure (DBP), and pulse pressure (PP) in east African families with at least 2 hypertensive siblings and living in the Seychelles islands (Indian Ocean). The sample consisted of 314 individuals (147 men and 167 women), both normotensive and hypertensive, from 76 pedigrees (meanϮSD of 4.1Ϯ2.8 persons per pedigree). After a 2-week off-treatment period, daytime and nighttime ambulatory blood pressure (BP) was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 24 publications
8
65
1
1
Order By: Relevance
“…Second, it was not tested whether the increase in 24-h BP heritability was statistically significant in these two studies. According to the study by Bochud et al ., 30 which provided the standard error of the estimated heritabilities, we found a large overlap between the 95%confidence interval of 24-h and office SBP heritabilities, which indicates that the increase in 24-h SBP heritability does not reach statistical significance. Third, an increase in heritability does not necessarily mean an increase in statistical power to find genes, because 24-h and office BP may be influenced by partly different genes.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Second, it was not tested whether the increase in 24-h BP heritability was statistically significant in these two studies. According to the study by Bochud et al ., 30 which provided the standard error of the estimated heritabilities, we found a large overlap between the 95%confidence interval of 24-h and office SBP heritabilities, which indicates that the increase in 24-h SBP heritability does not reach statistical significance. Third, an increase in heritability does not necessarily mean an increase in statistical power to find genes, because 24-h and office BP may be influenced by partly different genes.…”
Section: Discussionmentioning
confidence: 82%
“…To date, four twin studies 2528 and three family studies 2931 have reported heritability estimates for 24-h ABP recording. However, only three studies 25,30,31 reported the heritability estimates both for office and 24-h BP, with two family studies 30,31 observing higher heritability and one twin study observing similar heritability for 24-h BP. 25 For example, in the study by Fava et al ., 31 which included 260 siblings from 118 Swedish families, the heritability was 30% for 24-h SBP and 29% for 24-h DBP, whereas the heritability estimates for office BP were not significantly different from zero.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequent rapid population growth produced young isolates of 7-12 generations each. A more detailed description of the cohort stratification and the OFS design can be found in earlier reports (Bochud et al, 2005). Hypertension was diagnosed when subjects had a 24-hour SBP and/or DBP ≥135/85 mmHg (Pickering et al, 2005) or when they were on antihypertensive treatment.…”
Section: Methods and Study Designmentioning
confidence: 99%